Menyiasati Ideologi Neoliberal dalam Pendidikan - Ilyya Muhsin (Unisia, 2008)
When globalization has touched upon education, cultures, and economy, this means that there has been an expansion of western ideology and a brain washing of people in developing countries, such as Indonesia. Ironically, the government has legitimized the presence of foreign higher education in Indonesia. This creates a dilemma, because on one hand, this would make the quality of education of Indonesia more competitive and, on the other hand, could be used as a means of indoctrination of neo-liberalism. This article tries to discuss the fight against western ideology, developing in education, especially that related to the current issues.